2008
DOI: 10.1158/0008-5472.can-08-2600
|View full text |Cite
|
Sign up to set email alerts
|

Role of a Novel Splice Variant of Mitotic Arrest Deficient 1 (MAD1), MAD1β, in Mitotic Checkpoint Control in Liver Cancer

Abstract: Loss of mitotic checkpoint contributes to chromosomal instability, leading to carcinogenesis. In this study, we identified a novel splicing variant of mitotic arrest deficient 1 (MAD1), designated MAD1B, and investigated its role in mitotic checkpoint control in hepatocellular carcinoma (HCC). The expression levels of human MAD1B were examined in hepatoma cell lines and human HCC samples. The functional roles of MAD1B in relation to the mitotic checkpoint control, chromosomal instability, and binding with MAD2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 37 publications
(44 reference statements)
1
30
0
Order By: Relevance
“…Previous studies have shown that reduced expression of MAD1L1 promotes tumor development in mice, which further validates its tumor‐suppressing functions . This gene is over‐expressed in both HCC and breast cancer ; however, it is under‐expressed in chromophobe renal cell cancers . In the present study, only the methylation status of the MAD1L1 intron‐11 was analysed, and the MAD1L1 mRNA level was found to be similar between the MAD1L1 methylation‐low and ‐high HCCs.…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies have shown that reduced expression of MAD1L1 promotes tumor development in mice, which further validates its tumor‐suppressing functions . This gene is over‐expressed in both HCC and breast cancer ; however, it is under‐expressed in chromophobe renal cell cancers . In the present study, only the methylation status of the MAD1L1 intron‐11 was analysed, and the MAD1L1 mRNA level was found to be similar between the MAD1L1 methylation‐low and ‐high HCCs.…”
Section: Discussionsupporting
confidence: 81%
“…Sze KM et al have shown that all 6 hepatoma cell lines with defective mitotic checkpoint showed significant reduced expression of mitotic arrest deficient 2 ( Mad 2)[13]. Mad 1beta, a novel splicing variant of mitotic arrest deficient 1 ( Mad 1), was expressed at both mRNA and protein levels in the nine hepatoma cell lines tested and was over-expressed in 12 of 50 (24%) human HCC tissues[14]. Jeong SJ et al have shown that transcriptional dysfunction of hsMad 2 is frequently observed in hepatocellular carcinoma cells [15].…”
Section: Introductionmentioning
confidence: 99%
“…These transcriptional variants are often over-expressed, causing multipolar mitoses and mis-segregation in cancer cell lines and tissues. The MAD1ß and Aurora B isoforms provide excellent examples [44,45]; these isoforms lead first to errors in the mitotic spindle checkpoint and ultimately to CIN. Centrosome abnormalities are also caused by an imbalance in splice variants of proteins that are key centrosome regulators, like TrkAIII, which is over-expressed in advanced neuroblastoma and primary glioblastoma [46], and NEK2A [47], which has been proposed as a tumour marker and is abnormally expressed in most cancer cell lines and tumours.…”
mentioning
confidence: 99%